2004
DOI: 10.1016/j.immuni.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Niches Controlling B Lymphocyte Behavior within Bone Marrow during Development

Abstract: In bone marrow, hematopoiesis is thought to depend on special microenvironments known as niches that maintain blood cells. However, the identity of niches and interaction of blood cells with niches remain poorly understood. Here we identify stage-specific cellular niches for B lymphopoiesis. The earliest precursors, pre-pro-B cells and end-stage B cells, plasma cells require CXC chemokine ligand (CXCL)12. CXCL12-expressing cells are a small population of stromal cells, scattered throughout bone marrow and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
740
5
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 702 publications
(783 citation statements)
references
References 61 publications
30
740
5
8
Order By: Relevance
“…Likewise, as discussed above, BCMA can be activated by either April or BAFF 36. VCAM‐1 and ICAM‐1, the ligands of VLA‐4 and LFA‐1, are expressed by bone marrow stromal cells40 and, expectedly, in the bone marrow most if not all plasma cells contact stromal cells expressing VCAM‐1 41, 42. Mesenchymal stromal cells thus qualify as organizers of a survival niche for plasma cells, probably by providing essential survival signals, namely integrin‐mediated cell contact.…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, as discussed above, BCMA can be activated by either April or BAFF 36. VCAM‐1 and ICAM‐1, the ligands of VLA‐4 and LFA‐1, are expressed by bone marrow stromal cells40 and, expectedly, in the bone marrow most if not all plasma cells contact stromal cells expressing VCAM‐1 41, 42. Mesenchymal stromal cells thus qualify as organizers of a survival niche for plasma cells, probably by providing essential survival signals, namely integrin‐mediated cell contact.…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 93%
“…Of particular relevance for their attraction to the bone marrow within this timeframe is the chemokine CXCL12, a ligand for the chemokine receptor CXCR4 of plasma cells. CXCL12 is expressed by those mesenchymal stromal cells which the plasma cells contact in the bone marrow 41. The CXCR4 antagonist AMD3100 blocks the immigration of plasmablasts into and the establishment of memory plasma cells in the bone marrow, strongly suggesting that the plasma cells had been attracted to the stromal cells by CXCL1247.…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 99%
“…17 One of the soluble factors released by non-stem cell neighbors such as endothelial cells, osteoblasts, and other stromal cells of the bone marrow is stromal cell-derived factor-1 (SDF1). 18,19 The chemokine cysteine-X-cysteine receptor 4 (CXCR4) is a G proteincoupled seven-span transmembrane protein which binds SDF1 exclusively. 20,21 The SDF-1/CXCR4 axis plays an essential role in directing hematopoietic stem cells along a SDF1 gradient to their final niche in the bone marrow during ontogenesis, 22 but also in their mobilization into the peripheral blood.…”
Section: S Tellate Cells Reside Within the Perisinusoidal Space Ofmentioning
confidence: 99%
“…Several different BM cell types have recently been claimed as providing critical contributions to BMPC survival, including reticular stromal cells (7,8), osteoblasts (9), osteoclasts (10), Gr1 int CD11b + monocytes (11), eosinophils (12), megakaryocytes (MGKs) (13), and basophils (14). CXCL12-abundant reticular (CAR) cells, CXCL12 + reticular cells, and osteoblasts (15) were unambiguously demonstrated as key compartments of the BMPC niche when it was demonstrated that PCs lacking CXCR4 (the receptor for CXCL12) fail to home to the BM compartment (7).…”
mentioning
confidence: 99%